Advanced critical care nursing: a novel role with ancient history and unprecedented challenges worldwide - Papathanassoglou, Elizabeth (My University, 2011)
The acute care nurse practitioner (ACNP) role in critical care emerged because of the need for expert practitioners to provide care to patients with increased acuity levels and complex health conditions (Kleinpell, 2009a). Although, the role appeared to develop because of residency shortages in intensive care units (ICUs) (Keeling and Bigbee, 2005), it should not be viewed as an opportunity for nurses to relieve doctors of some of their increasedworkload. Rather it should be regarded as a predictable and long due restoration of nursing’s inherent attributes of clinical judgement and sovereignty, and as a superb chance to improve patients’ outcomes and to advance the culture of critical care
Keywords: Delivery of Health Care; Nurses; Intelligent medicine